Impact of type I Boston keratoprosthesis implantation on vision-related quality of life. Issue 7 (19th September 2017) - Ang, Marcus; Man, Ryan; Fenwick, Eva; Lamoureux, Ecosse; Wilkins, Mark
Abstract : Aim: To determine the impact of type I Boston keratoprosthesis (KPro) implantation on vision-related quality of life (VRQoL). Methods: Prospective study in 33 patients (mean age 56±12 years, 67% male) with bilateral corneal blindness, who underwent a KPro implantation at a single tertiary eye hospital (June 2011–July 2015). VRQoL was evaluated using the Impact of Vision Impairment Questionnaire (IVI) at baseline and at 3–6 months postsurgery, after stabilisation of best-corrected visual acuity (BCVA). Rasch analysis was used to transform the IVI responses into interval-level measures comprising the 'reading', 'mobility' and 'emotional' subscales with effect sizes calculated for pre-post VRQoL scores. Results: Mean preoperative BCVA was counting-fingers at 2 feet in the operated eye (20/240 fellow eye). Preoperative VRQoL scores: −2.27, –2.91 and −3.06 logits for the reading, mobility and emotional subscales, respectively. Device retention rate was 90% over the follow-up period (mean 26±12 months). We observed large gains for reading and mobility of 1.92 logits (effect size 0.88), and 2.64 logits (effect size 0.89) respectively, with a moderate gain in the emotional subscale of 2.11 logits (effect size 0.59). These improvements did not vary significantly with BCVA on multivariate analysis (all p>0.05). Conclusion: We observed a differential short-term improvement to VRQoL after KPro implantation with a significant impact on emotional well-being, which may not be fully explained by visual improvement alone. Further studies are required to confirm if these improvements in VRQoL are sustained in the long-term and are generalisable to other populations.